Proarrhythmic risk and determinants of cardiac autonomic dysfunction in collagen-induced arthritis rats. Issue 1 (December 2016) - Lin, Ting-Tse; Sung, Yen-Ling; Wu, Chih-En; Zhang, Hong; Liu, Yen-Bin; Lin, Shien-Fong
Abstract Backgrounds Patients with rheumatoid arthritis (RA) have increased risk of sudden cardiac death (SCD), which is two-fold higher than general population. The driving cause of SCD was considered due to lift-threatening arrhythmia where systemic inflammation acts as the pathophysiological basis linking RA to autonomicdysfunction. Methods To assess the sympathetic over-activity of "inflammatory reflex", we measured heart rate variability (HRV) in a rat collagen-induced arthritis (CIA) model, whose arthritis is induced in Lewis rats by intradermal injection of emulsion of type II collagen. Single-lead electrocardiogram (ECG) was recorded for 30 min every two days. Time and frequency-domain parameters, detrended fluctuation analysis (DFA), deceleration (DC) and acceleration capacity (AC) were analyzed. Results Compared with 9 control rats, many of HRV parameters of 9 CIA rats revealed significant different. At the beginning of arthritis, LF/HF was significant higher than controls (1st week: 2.41 ± 0.7 vs. 1.76 ± 0.6, p < 0.05; 2nd week: 2.24 ± 0.5 vs. 1.58 ± 0.5, p < 0.05) indicating intensive inflammatory reflex at the initial phase of inflammation but no significant difference was observed in the following recover phase. The similar trend of DFA parameters was noted. However, the DC appeared progressive lower despite of no significant increase of the LF/HF compared with controls since 4th week. Conclusions We observed sympathetic over-activation of inflammatory reflex during early stage of arthritis in CIA rats. The ongoing decline of DC indicated advanced cardiac autonomic dysfunction regardless of remission of acute arthritis.